The emigrants - Moberg, Vilhelm 1898-1973; Nordgren, Erik 1913-1992 (The Criterion collection, 2016)
A monumental mid-nineteenth century epic that charts, over the course of two films, a poor Swedish farming family's voyage to America and their efforts to put down roots in this beautiful but forbidding new world. Includes bonus disc with special features